Motivations for visiting and not visiting museums among young adults: A case study on UUM students - Mokhtar, Muhammad Fauzi; Kasim, Azilah (2011)
Marketing management is an important managerial dimension that must be continually assessed to ensure profit. It includes understanding target markets that could provide desired return to the organisation, but difficult to access.In the contexts of museums in Malaysia, this potentially lucrative but reluctant market is the youth market.This study looks at 1. the motivations of young adults for visiting museums, 2. the reasons inhibiting them from visiting museums, and 3. their perceptions on how museums should be marketed to attract young adults. It did so in the context of students in Universiti Utara Malaysia.Using a questionnaire survey, 1036 usable questionnaires were analyzed to fulfil the research objectives.The findings indicate that despite the observable low museum visitation among youth at national level, 82% of the respondents have actually visited at least one museum in the last three years.This indicate that youth in institutions of higher learning has higher predisposition to visit museums and could be a potential subsegment to target when marketing museums to young adults. In addition, a majority (70.5%) of respondents has an overall positive image of museums.This is contrasting the theory that young adults tend to see museums as boring, didactic and unapproachable.However, the motivations of visit found in this study are mainly practical in nature as young adults in the study context tend to visit museums to prepare homework or project, to broaden general knowledge, to attend school trip, to satisfy curiosity and to fill spare time. This shows that practicality can motivate young adults to visit museum. Among respondents who have never visited museums in the last three years, the main reason for not visiting was the lack of time, followed by lack of interest in museum, and lack of information about the museum offerings.Other reasons for not visiting museum include the preference for other activities, difficulties in getting required information about museums and the tendency to put off visiting until a later date and the perception that museum admission fees are too pricy.A very small percentage of the respondents simply indicated that they do not like to visit museum. From respondents feedback on museum marketing, brochuresappear to be an important information media for those young adults.They also want museums to have a strong web presence, have guides in the museums to assist visitors and have interesting events to increase the attractiveness of the museums to the target market.Money constraint could be the reason more than 90 percent of the respondents wanted to see lower admission fees. They also wanted collection in the museums to be exhibited in more attractive way and that museums online information in the government websites to be updated. All these suggestions are useful for museum marketers who are trying to reach and specifically target this young adults market segment.